On the Sensitivity of Collective Action to Uncertainty about Climate Tipping Points - Scott Barrett; Astrid Dannenberg (Center for Economic Studies and ifo Institute (CESifo), 2014)
Previous research shows that collective action to avoid a catastrophic threshold, such as a climate tipping point, is unaffected by uncertainty about the impact of crossing the threshold but that collective action collapses if the location of the threshold is uncertain. Theory suggests that behavior should differ dramatically either side of a dividing line for threshold uncertainty. Inside the dividing line, where uncertainty is small, collective action should succeed. Outside the dividing line, where uncertainty is large, collective action should fail. We test this prediction in the experimental lab. Our results strongly support the prediction: behavior is highly sensitive to uncertainty around the dividing line.
Keywords: C72; F51; H41; H87; Q54; 330; collective action; prisoners' dilemma; coordination game; threshold uncertainty; negotiations; tipping points; climate change; experimental economics